Implementation of Digital-Based Learning Media on Thematic Material on Students’ Scientific Abilities - Mansur, M.; Nurwahidin, Muhammad; Herpratiwi, Herpratiwi (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
Learning applied to elementary school-age children is very crucial, because the methods and processes of teaching teachers seem to force students to be able to achieve predetermined competencies. This research uses the (SLR) method. regarding research methods: "Literature" which means it is a critical analysis of the research that is being carried out on a special topic or in the form of a question to a part of science. helps us in compiling a framework that is in accordance with the theory, findings, and results of previous research in solving the problem exposure in the research conducted. The implementation of digital-based learning media on thematic material on scientific abilities can be used optimally, especially for elementary school level students, using digital-based media can certainly stimulate the cognitive, affective and psychomotor abilities of students, especially in accordance with the characteristics of 21st century learning where modern learning utilizes the sophistication of information and communication technology, the role of the teacher as a facilitator is very important in creating interesting and fun learning